2004
DOI: 10.1590/s0004-282x2004000100003
|View full text |Cite
|
Sign up to set email alerts
|

Value of extent of hippocampal resection in the surgical treatment of temporal lobe epilepsy

Abstract: The extent of hippocampal resection is associated with outcome. Incomplete resection of atrophic hippocampus may explain most surgical failures in patients with TLE due to unilateral hippocampal sclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 25 publications
3
22
0
1
Order By: Relevance
“…While experience with stereotactic laser amygdalohippocampectomy (SLAH) to date has suggested that seizure outcome may not be directly associated with total ablation volume, 3 further analysis has suggested that an ablation encompassing the majority of both the amygdala and hippocampus is associated with a greater chance of seizure freedom. 10,22 While these findings fall in line with the volumetric data from open surgery 13,14,16,17,23 other temporal lobe structures have yet to be involved in ablation cavity analysis of SLAH. As such, the ideal target and extent of ablation for SLAH has yet to be determined.…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…While experience with stereotactic laser amygdalohippocampectomy (SLAH) to date has suggested that seizure outcome may not be directly associated with total ablation volume, 3 further analysis has suggested that an ablation encompassing the majority of both the amygdala and hippocampus is associated with a greater chance of seizure freedom. 10,22 While these findings fall in line with the volumetric data from open surgery 13,14,16,17,23 other temporal lobe structures have yet to be involved in ablation cavity analysis of SLAH. As such, the ideal target and extent of ablation for SLAH has yet to be determined.…”
Section: Introductionsupporting
confidence: 54%
“…13 Since that time, several investigators have attempted to corroborate the above findings similarly employing MR imaging analysis, but with varied results. [14][15][16][17][18][19][20][21] The reason for this discrepancy is multi-factorial, not the least of which is that perioperative MR volumetric techniques are varied amongst investigators and thus, thwarts objective comparison amongst studies.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature we can find a lot of papers with controversial statements on the appropriate extent of surgical resections. Some authors stated that a larger extent of resection has influence on better seizure control [32,33] . Others have stated that the extent of resection is not the most important factor for the clinical seizure outcome [26,34,35] .…”
Section: Discussionmentioning
confidence: 99%
“…Although patients with TLE and neuroradiological evidence of hippocampal sclerosis have improved postsurgical outcomes relative to patients with TLE and no MRI lesion (Berkovic et al , 1995; McIntosh et al , 2004), between two-thirds and one-half of patients with hippocampal sclerosis will experience postoperative seizures (Berkovic et al , 1995; Janszky et al , 2005). Current suggestions for why these persistent postoperative seizures occur include a combination of insufficient resection of mesial temporal lobe tissue (Bonilha et al , 2004; Bonilha and Keller, 2015), mesial temporal lobe pathology existing outside the margins of resection (Babb et al , 1984; Holmes et al , 2000; Prasad et al , 2003; Keller et al , 2007), contralateral temporal lobe seizure involvement (Hennessy et al , 2000; Lin et al , 2005; Keller et al , 2007), occult extra-temporal lobe involvement, including temporal-plus epilepsy (Sisodiya et al , 1997; Ryvlin and Kahane, 2005; Kahane et al , 2015; Barba et al , 2016), structural network alterations (Bonilha et al , 2015; Keller et al , 2015 b ), and atypical subtypes of TLE that may be particularly resistant to conventional temporal lobe surgery (Blumcke et al , 2007; Thom et al , 2010; Bonilha et al , 2012). The development of predictive biomarkers for the future success of surgical intervention in epilepsy represents an important research endeavour, particularly as a reliable prognostic marker could inform patient clinical management and surgical decision-making.…”
Section: Introductionmentioning
confidence: 99%